East Timor – Bad Conscience of the International Community (Czech Journal of International Relations, 1997)
In the first decade of October 1996, he appointed the committee for awarding the Nobel Peace Prize the new laureates of this prestigious award of the Catholic bishop from East Timor Dili Carlos Filip Ximenes Bela and the leader of the local resistance against the Indonesian occupation of the former of the Portuguese territory of José Ramos Horta. He thus once again drew attention to the characteristically tragic episode of international relations of the last quarter of the 20th century- to a major case of devastating abuse of the decolonization process. Pone'Kud surprising nomination of the heroes of a little-known rezistence aroused a lively, if contradictory, response in the world and showed that the East Timorese cause is a fundamental challenge for the democratic world. Therefore, we consider it useful to recapitulate the history of the resistance, which has once again rightfully come to the forefront of world attention.